Respuesta :
Answer:
m = 60 years
Step-by-step explanation:
granddaughter's age in months is equal to her grandmother's age in years
d = m
The sum of the granddaughter's age in years and the grandmother's age in years is 65
d/12 + m = 65
Substitute
m/12 + m = 65
(13/12)m = 65
multiply both sides by 12/13
m = 65 * 12/13
m = 60 years
Answer:
60 years
Step-by-step explanation:
Let the age of grandmother be x years
So, age of granddaughter = x months = x/12 years
According to the question:
The sum of the granddaughter's age in years and the grandmother's age in years is 65.
[tex]x + \frac{x}{12} = 65 \\ \\ \frac{12x + x}{12} = 65 \\ \\ \frac{13x}{12} = 65 \\ \\ x = 65 \times \frac{12}{13} \\ \\ x = 60 \\ [/tex]
Thus, the age of grandmother is 60 years.